2016
DOI: 10.1186/s12884-016-0969-x
|View full text |Cite
|
Sign up to set email alerts
|

Adopting a healthy lifestyle when pregnant and obese – an interview study three years after childbirth

Abstract: BackgroundObesity during pregnancy is increasing and is related to life-threatening and ill-health conditions in both mother and child. Initiating and maintaining a healthy lifestyle when pregnant with body mass index (BMI) ≥ 30 kg/m2 can improve health and decrease risks during pregnancy and of long-term illness for the mother and the child. To minimise gestational weight gain women with BMI ≥ 30 kg/m2 in early pregnancy were invited to a lifestyle intervention including advice and support on diet and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 41 publications
7
29
0
Order By: Relevance
“…Recollections of the first phase of targeting revolved around the themes of being identified as a target group based on weight, and agreeing to join interventions. In line with previous studies of women partaking in interventions and health‐care initiatives, we found that being approached on the basis of high BMI was remembered, not as something negative, but rather as an offer of help, or as something undertaken through genuine concern about the women and their children. However, in our study, some women also recalled that, in being identified, they felt as though they were negatively stereotyped.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Recollections of the first phase of targeting revolved around the themes of being identified as a target group based on weight, and agreeing to join interventions. In line with previous studies of women partaking in interventions and health‐care initiatives, we found that being approached on the basis of high BMI was remembered, not as something negative, but rather as an offer of help, or as something undertaken through genuine concern about the women and their children. However, in our study, some women also recalled that, in being identified, they felt as though they were negatively stereotyped.…”
Section: Discussionsupporting
confidence: 88%
“…The mothers in our study found that their participation in the intervention during pregnancy had very little long‐term significance: they had not achieved a lasting lifestyle change for themselves or their families. This finding is supported by a qualitative study from Sweden, which, to our knowledge, is the only other retrospective study on this topic. This, too, found that women had difficulty maintaining lifestyle change post‐natally as a consequence of work, stress, childcare and relationships with their partners .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…When considering previous studies on determinants of lifestyle behavior conducted in women of childbearing age, survey studies showed that women wishing to become pregnant were interested in lifestyle programs, especially when tailored to the possibilities within the daily life of women [14,15]. During pregnancy, health of the unborn child was an important motivator for adopting a healthy lifestyle [16][17][18]. On the other hand, pregnant women mentioned that being pregnant is a justification for not worrying about weight and pregnancy is a time to eat for two [16].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%